A New Species Belonging to the Cyrtodactylus sadleiri Complex (Squamata: Gekkonidae) Has Been Discovered in East Java, Indonesia - Riyanto, Awal; Sidik, Irvan; Hamidy, Amir; Grismer, L. Lee; Abinawanto (Zootaxa, 2025)
We describe a new species of Cyrtodactylus Gray from East Java (Maospati and Mojokerto), Indonesia that belongs to the C. sadlieri complex within the C. darmandvillei species group. It is a medium sized (SVL) species with adult males reaching 67.2 mm and females 59.0 mm, dorsal tubercles absent on brachium, present on antebrachium and along the ventrolateral fold; 18–20 irregular dorsal tubercle rows at midbody; 26–28 paravertebral tubercles per series; 28–34 ventral scale rows across belly; precloacal groove present with 32–37 precloacofemoral pores in males; enlarged femoral and precloacal scales arranged in a continuous series; abrupt transition between the enlarged femorals and the adjacent scales on the posterior margin of the thigh; subequal median subcaudal scales not transversely enlarged. The new species is genetically divergent from the other Javan congeners of the C. darmandvillei groupwith genetic divergences (p-distances) ranging from 7.7–12.1% for the mitochondrial ND2 gene.